Nuremberg Laws - Daniel Krošlák (Societas et Iurisprudentia, 2013)
Anti-Semitism as the official government policy in Germany has been enforced before the adoption of the Nuremberg racial laws of September 15th, 1935 (the first anti-Semitic regulation is considered to be the Law for the Restoration of the Professional Civil Service, passed on April 7th, 1933). The Nuremberg racial laws – the Reich Citizenship Law and the Law for the Protection of German Blood and German Honor – have been prepared very hastily and did not address several issues (e.g. the definition of “Jew”). In the following years several supplementary decrees were therefore adopted and other laws were passed those have opened the space for implementation of anti-Jewish policy, which have culminated into a systematic genocide of Jews in Europe (Endlösung der Judenfrage).